The age and mode of presentation of benign prostatic hyperplasia at Hubli in Karnataka - Prasad, H. L.; Madakatti, B. S.; Manjunath, M. L. (International Journal of Research in Medical Sciences, 2017)
Background: The peculiarities of the prostate are that in old age when most of organ regresses in size it enlarges and causes trouble. By virtue of its position, it guards outlet of urinary bladder. It must be admitted that even today the extent nature of etiology, pathogenesis and diagnosis are all-debatable. Therefore, the present study was aimed at elucidating the age and mode of Benign Prostatic Hyperplasia among the patients in and around Hubli, Karnataka. Methods: The study was conducted after the institutional ethical committee approval and written informed consent from all the patients. 21 cases of BPH were included in the present study. The signs and symptoms of mode of presentation were recorded. The urine was examined for the presence of albumin, pus cells, epithelial cells and RBCs. Results: The maximum incidence of the disease was in the age group of 60-69 years. Majority of the patients had difficulty in micturition followed by increased frequency of micturition both during day and night Patient with retention usually had distension of bladder. These patients complained of dull aching pain in the suprapubic area and in the groin region. Burning micturition (14.28%), dribbling of urine (4.76%), urgency (4.76%), and haematuria (4.76%) were present. Routine urine examination showed albumin (28.56%), pus cells (23.80%), epithelial cells (19.04%) and haematuria (4.76%). Conclusion: Incidence of BPH at Hubli region of Karnataka is 0.3001% of total hospital admission. The maximum age incidence of BPH is in the age group of 60-69 years. Majority of the patients had difficulty in micturition increased frequency of micturition both during day and night a large number of cases show association with presence of urinary tract infection.